2018
DOI: 10.1155/2018/7103219
|View full text |Cite
|
Sign up to set email alerts
|

The Proportion of Regulatory T Cells in Patients with Systemic Lupus Erythematosus: A Meta-Analysis

Abstract: Background Accumulating evidence indicates that a deficiency in or dysfunction of regulatory T cells (Tregs) is involved in the pathogenesis of systemic lupus erythematosus (SLE). As different markers have been used to identify Tregs, recent studies on the proportions of Tregs in SLE patients have generated controversial results. To clarify the status of Tregs in such patients, we determined the proportions of Tregs present during development of the disease, with special consideration of controversial cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 69 publications
0
22
1
Order By: Relevance
“…However, studies about CS and DMARDs on peripheral blood Tregs in AS patients are still lacking. In addition to drugs, disease activity also affects the proportion of peripheral blood Tregs [81, 82]. But our subgroup analysis found no difference in the proportion of Tregs in patients with active compared with stable AS.…”
Section: Discussionmentioning
confidence: 92%
“…However, studies about CS and DMARDs on peripheral blood Tregs in AS patients are still lacking. In addition to drugs, disease activity also affects the proportion of peripheral blood Tregs [81, 82]. But our subgroup analysis found no difference in the proportion of Tregs in patients with active compared with stable AS.…”
Section: Discussionmentioning
confidence: 92%
“…[23][24][25] A recent meta-analysis found that the proportion of Tregs in patients with active SLE was lower than that in patients in remission, suggesting that SLE activity is related to a decrease in Treg numbers. 26 Similarly, Miao et al 9 showed that a decrease in the absolute number of circulating CD4 + Tregs, rather than an increase in either the absolute number or proportion of Th17 cells, crucially affected the immune disorders of pSS patients; pSS is also a chronic, autoantigenmediated inflammatory disease. Tregs inhibit the proinflammatory activity of macrophages, which are the principal immune effector cells in patients with TNFmediated psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zhang et al (51) performed a systemic review on a similar topic, but mainly focused on establishing the alteration of Treg frequency in SLE. However, in our meta-analysis the changes in the frequency and absolute number of Tregs were calculated along with a systemic analysis of the effects of treatment, disease severity, and organ involvement on Tregs.…”
Section: Discussionmentioning
confidence: 99%